Utilization of Water Lettuce (Pistia stratiotes L) Leaf Meal FermentedUsing Cow Rumen Liquor in Dieton Growth of Nilem (Osteochilus hasselti) Fingerling - Irma Apri Nanda; Indra Suharman; Adelina ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research wasconducted for 56 days from February toMarch2017. The aim of this research is to determine the number ofwater lettuce leaf meal fermented using cow rumen liquo (FWLL) in drets on growth and feed efficiency of Nilem (O.hasselti).This study used completely randomized design (CRD) with five treatments and three replications. 300 fingerlings of O..hasselti(initial weight 12 g ) randomly divided into 15 net cages were fed five different experimental 30 % isonitrogenous diets, a control ( O%  FWLL ) meal,and four diets containing different substitution levels of FWLL meal (10, 20, 30 and 40 % , respectively) in place of soybean meal (SBM) as protein source. The results shows that fish fed with 30% FWLL meal substitution level perform the best results among four experimental diets. Based on the results of present research, 30% substitution level of FWLL meal as SBM substitution is recommended in pradical diet of O.hasselti fingerling for growth performance. Keywords: cow rumen liquor, fermentation, Osteochilus hasselti, water lettuce leaves